The presence system and the intersectoral management in education: exploratory dialogue about the “bolsa família” program (PBF) in schools located in the border region - Martins, Luciano Marques da Costa (2017)
This paper aims to describe the limits and potentialities of the “Bolsa Família Program” - PBF, based on the Presence System, which is an intersectoral management resource for compliance conditionality monitoring in education. This descriptive and exploratory research uses the simple descriptive statistics for data exploration of the Presence System. It uses the PBF report technician as well, who is responsible for the program in the city of Ponta Porã, Mato Grosso do Sul, Brazil, to construct the information under analysis. It has been observed that PBF is a powerful reducer of school dropout in the border region, but it is not enough to totally eliminate this problem and the school failure. It is suggested that investments policies development and agreement, programs and legislation aimed to meeting the specificities existing at the Brazilian dry border with Paraguay.